2014
DOI: 10.1002/cctc.201300907
|View full text |Cite
|
Sign up to set email alerts
|

How to Modulate Catalytic Properties in Nanosystems: The Case of Iron–Ruthenium Nanoparticles

Abstract: Ultrasmall FeRu bimetallic nanoparticles were prepared by co‐decomposition of two organometallic precursors, {Fe[N(Si(CH3)3)2]2}2 and (η4‐1,5‐cyclooctadiene)(η6‐1,3,5‐cyclooctatriene)ruthenium(0) (Ru(COD)(COT)), under dihydrogen at 150 °C in mesitylene. A series of FeRu nanoparticles of sizes of approximately 1.8 nm and incorporating different ratios of iron to ruthenium were synthesized by varying the quantity of the ruthenium complex introduced (Fe/Ru=1:1, 1:0.5, 1:0.2, and 1:0.1). FeRu nanoparticles were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 86 publications
1
20
0
Order By: Relevance
“…Low values of ca. 0.4 H/Ms were observed for FeRu NPs as the consequence of the dilution of Ru atoms by Fe ones at the surface of the NPs [254]. Fe NPs were reported to have between 0.4 and 0.6 H/Fes thus evidencing the metallic character of these particles [255].…”
Section: Characterization and Reactivity Of Hydrides At Metal Nanoparmentioning
confidence: 97%
“…Low values of ca. 0.4 H/Ms were observed for FeRu NPs as the consequence of the dilution of Ru atoms by Fe ones at the surface of the NPs [254]. Fe NPs were reported to have between 0.4 and 0.6 H/Fes thus evidencing the metallic character of these particles [255].…”
Section: Characterization and Reactivity Of Hydrides At Metal Nanoparmentioning
confidence: 97%
“…The performance of bimetallic clusters can be tuned by controlling their structures, components and sizes. Transition metal clusters doping with a different transition metal have been studied to devise the desired catalytic, optical, electronic, and magnetic applications in materials science, microelectronics, and medical science [8][9][10][11]. Sauvage and coworkers investigated mechanical properties of Cu/V nanocomposite wire by both scanning transmission electron microscopy and atom probe tomography [12].…”
Section: Introductionmentioning
confidence: 99%
“…The main preparation routes for FeRu alloys involve co-impregnation of a solid support with solutions of metallic salts, ionic liquids and their reduction [27][28][29][30], microwave irradiation [26,31] or metal organic chemical vapor deposition (MOCVD) [32]. Very recently, Kelsen et al reported a new organometallic approach for the synthesis of FeRu bimetallic nanoparticles under mild conditions [33,34]. This approach which is based on the reduction of various organometallic precursors in the presence of a reducing agent under mild conditions was originally developed in the Toulouse group for the synthesis of monodisperse magnetic nanoparticles which can be mono or bimetallic [35][36][37], or even associated with a main group element to form e.g.…”
Section: Introductionmentioning
confidence: 99%
“…carbides [38]. Thus, for the synthesis of iron-based nanoparticles, the iron bis(amide) complex {Fe[N(SiMe 3 ) 2 ] 2 } 2 (Me = CH 3 ) was chosen due to its reactivity and versatility for producing welldefined nanostructures with unprecedented magnetic [35][36][37][38][39][40][41][42][43][44], catalytic [33,34] or hyperthermia properties [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation